2012
DOI: 10.4238/2012.april.27.5
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial D-loop nucleotide diversity in Astyanax (Osteichthyes, Characidae) from the upper Paraná and upper Paraguay River basins

Abstract: ABSTRACT. The morphological discrimination between the speciesAstyanax altiparanae and A. asuncionensis of the upper Paraná River and Paraguay River basins, respectively, has always been difficult. Two D-loop haplogroups of A. altiparanae are known, one with the presence (AltoPR) or the absence (AltoPR-D) of a 32-bp block similar to that in A. asuncionensis. We examined these samples to characterize A. altiparanae

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Sequences revealed the two haplogroups already reported by Prioli et al (2012), with an insertion or deletion events of 35 bp. Although Prioli et al (2012) reported a 32-bp indel, the difference seems to have been caused by a variation in sequence alignment.…”
Section: Resultsmentioning
confidence: 82%
See 4 more Smart Citations
“…Sequences revealed the two haplogroups already reported by Prioli et al (2012), with an insertion or deletion events of 35 bp. Although Prioli et al (2012) reported a 32-bp indel, the difference seems to have been caused by a variation in sequence alignment.…”
Section: Resultsmentioning
confidence: 82%
“…Sequences revealed the two haplogroups already reported by Prioli et al (2012), with an insertion or deletion events of 35 bp. Although Prioli et al (2012) reported a 32-bp indel, the difference seems to have been caused by a variation in sequence alignment. The specimen AstyPR-04 was reported with a 35-bp segment but with a nucleotide polymorphism compatible to that of haplogroup AltoPR-D, which does not feature the 35-bp segment.…”
Section: Resultsmentioning
confidence: 82%
See 3 more Smart Citations